Political Participation of Female in Pakistan: Prospects and Challenges - Begum, Azeema (Universitas Islam Indonesia, 2023)
Owing to gender imbalances and the patriarchal system, females in Pakistan are considered minorities in the political process. The quota system has increased female representation in the parliament. Nonetheless, it is imperative to implement effective strategies and policies to empower women and to improve their engagement in Pakistani politics. The main objective of this study was to explore the major challenges and prospects of female participation in politics in Pakistan. Additionally, this study investigates the obstacles and opportunities for female participation in leadership. A qualitative research method was adopted in this study, relying on a desk-study approach and utilizing various secondary sources such as articles, research papers, government reports, and official websites. The main findings of the study indicate that economic dependency, lack of education and literacy, gender segregation, male domination, traditional beliefs, financial issues, limited awareness of political rights, political parties, social and cultural norms, and religious interpretation are the major challenges faced by women in Pakistan when it comes to participating in the democratic process and governance system. Furthermore, the underrepresentation of women in politics reflects complex and mutually reinforcing social dynamics, highlighting the need for concerted and collaborative actions and measures to address these challenges. In conclusion, women's participation will lead to improved decision-making concerning gender-based laws and regulations in various sectors, including education, health, the workplace, and society.